Exploring the Relationship between Mainstreet and University Students: A Case Study of a Small University in a Small Town - Andy Bertsch; Brett Hlebechuk; Mohammad Saeed; James Ondracek; Tristan Maldonado; Dorion Cipriani; Adesuwa Erude; Katie Mayer; Masaya Ito (International Journal of Organizational Business Excellence, 2022)
The research has been conducted to gain insight and understanding of how downtown culture is perceived by college students. The data collected were from students at a small university in a small town of fewer than 50,000 people. Of the 120 responses, 30% came from students who were originally from city, 26% came from students from somewhere else in the state, 22% came from students that were originally from somewhere else in the country besides the state, and 17% are from international students. The research employed a 28-question survey based on personal opinion of downtown culture and how involved students are there in the said culture. The results indicate that it would be very beneficial if downtown area held more events that are open to the whole community. It is especially important to hold events that include our diverse population of people who are from out of state or from a country abroad that are similar to military appreciation events. The future studies may investigate community/university student partnerships through interdisciplinary outreach and participation as well as service-learning. The universities can play a significant role as innovation and research hubs, bringing together public, commercial, and non-profit institutions.